2013
DOI: 10.1590/s0103-21002013000400016
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre as intervenções de enfermagem realizadas e os registros em sistema informatizado para atenção básica

Abstract: Objective: Compare the interventions performed by the nursing staff in a Primary Health Care Unit with the interventions recorded in the information system. Methods: Descriptive, exploratory study conducted in two stages at a Health Unit considered as having good practices in nursing. Stage 1: direct, non-participatory and structured observation for five days. Stage 2: application of the cross-mapping technique in the activities recorded in the computerized system, adapting them in standardized language for nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…In that sense, a study appointed that the information system at the FHS contains insufficient spaces to report on the nursing team's work, showing the importance of qualifying the information systems developed to support the planning of nursing staffing needs ( 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, a study appointed that the information system at the FHS contains insufficient spaces to report on the nursing team's work, showing the importance of qualifying the information systems developed to support the planning of nursing staffing needs ( 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Failure to use clinical thinking influences decision making and interferes in care quality (14) . However, if correctly employed, digital records make it possible to direct nursing action (18) and frequently review care plans and necessary changes (19) , aspects that favor communication in multi-disciplinary teams, clinical thinking and relevant decision making (20) . Nurses reported that they assess care demands through nursing visits, subjective assessments of care complexity, medical diagnoses and anamnesis during admission.…”
Section: Discussionmentioning
confidence: 99%
“…Outro aspecto relacionado ao cálculo da carga de trabalho anual refere-se aos dados de produção referentes ao ano anterior. Questiona-se aqui se o sistema atual de registro das informações de USF, Sistema de Informação da Atenção Básica (SIAB) disponibiliza os dados necessários para o cálculo, bem como o trabalho desenvolvido por todos os profissionais, visto que o estudo mostrou que o SIAB apresenta campos insuficientes para relatar o trabalho realizado pela equipe de enfermagem em USF (168) . Estudos na literatura, com aplicação do WISN em diferentes realidades internacionais utilizam diversas fontes de dados para o cálculo do tempo das atividades.…”
Section: Método Wisnunclassified